Dietary patterns and cardio-cerebrovascular disease in a Chinese population - Wang, H., Baoji Center for Disease Control and Prevention, Shaanxi, China; Qu, M., Baoji Center for Disease Control and Prevention, Shaanxi, China; Yang, P., Baoji Center for Disease Control and Prevention, Shaanxi, China; Yang, B., Baoji Center for Disease Control and Prevention, Shaanxi, China; Deng, F., Baoji Center for Disease Control and Prevention, Shaanxi, China (Nutrition research and practice, 2015)
BACKGROUND/OBJECTIVES: Dietary pattern and its association with cardio-cerebrovascular disease have not been studied in Baoji city by now. This study was aimed to identify the dietary patterns among Chinese adults in Baoji, and explore the association between these dietary patterns and cardio-cerebrovascular disease. SUBJECTS/METHODS: A total of 4,968 participants were included in this study at 12 counties. With multistage stratified random sampling and semi quantitative food frequency questionnaire, the prevalence of cardio-cerebrovascular disease and dietary intake were investigated in 2013. We used factor analysis to establish dietary patterns. RESULTS: A total of 4,968 participants over 15 years old were included in this study. Five dietary patterns were identified in Baoji: protein, balanced, beans, prudent, and traditional patterns. The protein dietary pattern mainly included animal and plant proteins and was negatively associated with hypertension as well as stroke. The balanced pattern included carbohydrates, protein, and fat and was negatively associated with hypertension as well as stroke. The beans pattern was mainly beans and beans products and was negatively associated with hypertension. The prudent pattern only included staple foods and pickled vegetables and was positively associated with hypertension as well as coronary heart disease. The traditional pattern was representative of local Baoji traditional recipes and was positively associated with hypertension. CONCLUSIONS: The protein, balanced, and beans dietary patterns showed many protective effects on cardio-cerebrovascular disease. Based on these results, Baoji city residents should be encouraged to choose protein, balanced, and beans dietary patterns and abandon prudent and traditional patterns to prevent incidence of hypertension, coronary heart disease, and stroke.